Kebahagiaan Remaja Panti Asuhan (Jurnal Ilmiah Psikologi MIND SET, 2020)
This research aims to study on how teenagers that live in orphanages describe their happiness, although not living with their families. The participants of this research consist of 4 teenagers that live in Salib Putih orphanage with an age range of 15-18 years old. The method applied in this research is the Intrinsic Case Study method with interviews and observations being the method of collecting data. From the result of the data analysis, the researcher found that teenagers who live in orphanages have the concept of happiness which connects to social relations, namely their families or peers. Besides that, their happiness include a problem-free life, adapting skills, living in a supportive environment, and being loved by their parents. The sources of their happiness consist of their hobbies, the capability to regulate their emotions, and that they are able to meet their parents. The perception of their environment, sufficient necessities, the ability to pursue education, gratitude and forgiveness, future orientation, and optimism regarding the future are also important factors of their concept of happiness.